Le « théâtre scientifique » au xixe siècle : usages esthétiques, pédagogiques et sociopolitiques du spectacle de la science - Amélie Calderone (Itinéraires)
In a century of booming scientific discoveries, Antoine Andraud and Louis Figuier presented themselves as the fathers of an innovative dramatic form. Combining education and drama, their “scientific theatre” aimed to accomplish an aesthetic, cultural and social revolution. The ambition was to connect theater, which was then a key media, with science, which development was spectacular at the time, in order to serve pedagogic purposes. This endeavor to popularize science in a new way took its source in the romantic renewal of aesthetic forms. These attempts were not successful : the texts remained in most cases “paper plays”, but they were in reality a mere pretext to support ideological and political projects. In this light, they are now regarded as a key to understanding the connections between theatre, science and society in the 19th century.